Anterior mediastinal mass 4 years after type A aortic dissection. Issue 1 (31st January 2019) - Wallace, Alison; Marcuzzi, Danny; Ko, Micheal; Latter, David
Abstract: A 47-year-old male who previously underwent emergency surgery for type A aortic dissection presented to the emergency department 4 years later with acute chest pain radiating to his back and a significant drop in hemoglobin. Clinical presentation was concerning for aortic graft failure, but imaging revealed a large (6.0 × 3.2 × 12.8 cm 3 ) soft tissue mediastinal mass that was not present 4 years before. Pathologic analysis revealed a rare thymic cyst with a hemorrhagic component. This was a challenging case from diagnostic and operative perspectives, involving the expertise of both cardiac and thoracic surgical teams.